Self-monitoring in hypertension: a web-based survey of primary care physicians. - McManus, R; Wood, S; Bray, E; Glasziou, P; Hayen, A; Heneghan, C; Mant, J; Padfield, P; Potter, J; Hobbs, F (2014)
Although self-monitoring of blood pressure is common among people with hypertension, little is known about how general practitioners (GPs) use such readings. This survey aimed to ascertain current views and practice on self-monitoring of UK primary care physicians. An internet-based survey of UK GPs was undertaken using a provider of internet services to UK doctors. The hyperlink to the survey was opened by 928 doctors, and 625 (67%) GPs completed the questionnaire. Of them, 557 (90%) reported having patients who self-monitor, 191 (34%) had a monitor that they lend to patients, 171 (31%) provided training in self-monitoring for their patients and 52 (9%) offered training to other GPs. Three hundred and sixty-seven GPs (66%) recommended at least two readings per day, and 416 (75%) recommended at least 4 days of monitoring at a time. One hundred and eighty (32%) adjusted self-monitored readings to take account of lower pressures in out-of-office settings, and 10/5 mm Hg was the most common adjustment factor used. Self-monitoring of blood pressure was widespread among the patients of responding GPs. Although the majority used appropriate schedules of measurement, some GPs suggested much more frequent home measurements than usual. Further, interpretation of home blood pressure was suboptimal, with only a minority recognising that values for diagnosis and on-treatment target are lower than those for clinic measurement. Subsequent national guidance may improve this situation but will require adequate implementation.